2014
DOI: 10.1016/j.ijhydene.2014.04.189
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen production from biomass and plastic mixtures by pyrolysis-gasification

Abstract: The addition of plastics to the steam pyrolysis/gasification of wood sawdust with and without a Ni/Al 2 O 3 catalyst was investigated in order to increase the production of hydrogen in the gaseous stream. To study the influence of the biomass/plastic ratio in the initial feedstock, 5, 10 and 20 wt. % of polypropylene was introduced with the wood in the pyrolysis reactor. To investigate the effect of plastic type, a blend of 80 wt. % of biomass and 20 wt. % of either polypropylene, high density polyethylene, po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
95
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 229 publications
(108 citation statements)
references
References 40 publications
(53 reference statements)
4
95
0
Order By: Relevance
“…Reduction of the catalyst occurred in-situ by the generated process gases, particularly hydrogen and carbon monoxide [27].…”
Section: Methodsmentioning
confidence: 99%
“…Reduction of the catalyst occurred in-situ by the generated process gases, particularly hydrogen and carbon monoxide [27].…”
Section: Methodsmentioning
confidence: 99%
“…Steam reforming of coal and biomass can be used for the production of hydrogen and if the CO is converted to CO2 and the total CO2 solvent extracted and captured, then low carbon hydrogen can be generated from coal or biomass [3][4][5]. In the combustion of rich mixtures of biomass, as studied in this work, the equilibrium products are essentially those of a gasification process with high CO and H2 [6].…”
Section: Biomass and Hydrogen Productionmentioning
confidence: 99%
“…Hence, it can be concluded that Ni/ Generally, the process of gasification is favored by the high temperature which amplifies the secondary hydro cracking and shifts the reactions to conversion of hydrocarbons (C n H 2n ). This particular fact might be because of the contribution of the reforming reactions which are favored and occurred at high temperature, hence becoming prevailing at temperatures which are higher than 800°C [43][44][45][46][47][48][49][50]. The finite gas composition is a function of the common reactions that at the same time come off by increasing the synthesis gas yields connected with the conversion of tar into synthesis gas.…”
Section: Catalytic and Non-catalytic Activitymentioning
confidence: 99%